The effect of heat treatment on the lactosylation of milk proteins - Jing Lu; Tong Zhu; Ying Dai; Lina Xing; Liu Jinqi; Sumei Zhou; Chunli Kong (Journal of Dairy Science, 2023)
ABSTRACT: Protein lactosylation is a significant modification that occurs during the heat treatment of dairy products, causing changes in proteins' physical-chemical and nutritional properties. Knowledge of the detailed lactosylation information on milk proteins under various heat treatments is important for selecting appropriate thermo-processing and identifying markers to monitor heat load in dairy products. In the present study, we used proteomics techniques to investigate lactosylated proteins under different heating temperatures. We observed a total of 123 lactosylated lysines in 65 proteins, with lactosylation even occurring in raw milk. The number of lactosylated lysines and proteins increased moderately at 75°C to 130°C, but dramatically at 140°C. We found that 6 out of 10, 9 out of 16, 6 out of 12, and 5 out of 15 lysine residues in κ-casein, β-lactoglobulin, α-lactalbumin, and αS1-casein, respectively, were lactosylated under the applied heating treatment. Moreover, different lactosylation states of individual lysines and proteins can indicate the intensity of heating processes. Lactosylation of K14 in β-lactoglobulin could distinguish pasteurized and UHT milk, while lactosylation of lactotransferrin can reflect moderate heat treatment of products.